Social Criticism in Poetry Fairy Tale of a Sun Picker by Indah - Iskandar, Ramadhan Attalarik; Sumiyadi; Rudi Adi Nugroho; Halimah (al-Afkar, Journal For Islamic Studies, 2024)
This research was raised based on problems related to social criticism in the poem Fairy Tale of a Sun Picker by Indah. The method the researcher used in the research was descriptive qualitative with a literary sociology model approach. The results of this research include six data findings related to social criticism in the poem Fairy Tale of a Sun Picker by Indah, namely about: humans who look cynically; scavengers looking for used mineral water bottles, traveling salesmen with dirty towels, and officials who are clever with words; humans who throw rubbish carelessly; paid public toilets used by market workers, as well as the sweat mixed with sadness from an elderly grandfather whose child committed suicide; the arbitrary behavior of the rulers towards the people; and plastic rice which was once distributed illegally in Indonesia. The conclusion of this research states that the literary sociology model can examine the social criticism contained in the poem Fairy Tale of a Sun Picker by Indah in depth.